Do multiple parents help or hinder international joint venture performance? The mediating roles of contract completeness and partner cooperation - Gong, Yaping; Shenkar, Oded; Luo, Yadong; Nyaw, Mee Kau (Strategic Management Journal, 2007)
Abstract We develop a mediation model in which the number of partners in a joint venture affects venture performance through contract completeness and partner cooperation. In a sample of 224 international joint ventures, we find that the number of partners is negatively related to venture contract completeness and partner cooperation, both of which are positively related to joint venture performance. The number of partners is inversely related to joint venture performance and the relationship is mediated by contract completeness and partner cooperation. We discuss theoretical and managerial implications for joint venture research and practice. Copyright © 2007 John Wiley & Sons, Ltd.